Variability and reliability of times registered for cesarean delivery surgical processes at a private clinic, Lima, Peru, 2011 - Virú-Loza, Manuel André (2013)
Efficiency evaluation is a useful tool for making right decisions at health care institutions. This includes knowing the variability and reliability of registered medical and surgical procedures times. Objectives: To determine variability and confidence of registered cesarean deliveries surgical processes times. Design: Cross-sectional study. Institution: Clinica Centenario Peruano Japonesa. Participants: Patients’ cesarean deliveries registries. Interventions: Medical and surgical times data were obtained from the surgical registry and clinical records' registry, 2011. Main outcome measures: Dispersion measures of all indicators and intraclass correlation coefficients (ICCs) from the studied registries. Results: Operating room patient transfer time showed the greatest variability and the ICCs between studied registries for starting and ending time of cesarean delivery were 0.902 and 0.901, respectively. Conclusions: At the private clinic studied patient transfer to the operating room was the most varied, and there was good reliability between operatory registries and clinical records' registries. Efficiency and productivity analyses to improve surgical processes need to be published in order to be useful to other health care centers.